Pengaruh Kepercayaan Konsumen Dan Kualitas Produk Terhadap Keputusan Pembelian Pelembab Wajah Skintific Di Bekasi - Inggi Widianingsih; Nidaul Izzah (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.Consumer purchasing decisions are influenced by various factors, among which consumer trust andproduct quality were particularly prominent. Skintific is a well-known brand of facial moisturizer among theresidents of Bekasi; however, it faced intense competition in the skincare market. This study aimed toexamine the influence of consumer trust and product quality on the purchase decisions of Skintific facialmoisturizers in Bekasi. The research employed a quantitative method with an associative approach. Thesample comprised 150 respondents, selected through accidental sampling. Data were collected usingquestionnaires and analyzed through multiple linear regression. The findings indicated that both consumertrust and product quality had a positive and significant influence on purchase decisions, both partiallyand simultaneously. In partial analysis, consumer trust contributed 27.2%, while product qualitycontributed 49.6% to purchase decisions. Simultaneously, these two variables accounted for 76.8% of theinfluence on purchase decisions, whereas the remaining 23.2% was attributed to other variables notexamined in this study.Keywords: Consumer Trust, Product Quality, Purchase Decision